Increasing Students' Scientific Literacy Competence Through A Stem-Based PjBL Learning Model: A Case Study of an Ecosystem Project - Fitri Yuliawati; Endang Sulistyowati; Anita Ekantini; Inggit Dyaning Wijayanti (Postgraduate, University of Mataram, 2024)
Scientific literacy has an important role in equipping individuals to be sensitive to the environment and actively participate in making decisions regarding existing environmental issues. This research aims to test the effectiveness of the STEM-based Project-Based Learning (PjBL) learning model in increasing the scientific literacy of PGMI students in science courses. This research uses an experimental method with a one group pretest-posttest design. The research subjects were 41 students selected using cluster random sampling technique. The instruments used in this research include a scientific literacy test instrument and an observation sheet on the implementation of PjBL-STEM learning. The findings of this research show that learning through PjBL-STEM on Ecosystem material facilitates students in solving existing environmental problems in the form of STEM-based projects. The results of the T-Paired test have a sig.2-tailed value of 0.000<0.05, indicating that there is a significant difference in the scientific literacy results of PGMI students in science courses. Based on the N-Gain analysis, a score of 0.5 shows that the STEM-based PjBL learning model is effective in increasing the scientific literacy of students in the medium category.